Prevalence of Gastrointestinal Parasites in Goat (Capra hircus) of Malarani Rural Municipality, Arghakhanchi District of Nepal - Sah, Naresh Kumar (Nepalese Journal of Agricultural Sciences, 2025)
Gastrointestinal parasitic infection in goat is one of the causes of low productivity, morbidity and mortality. This study was conducted to determine the prevalence, intensity of infection and farm management system. Faecal samples were collected from 200 goats from Malarani Rural Municipality, Arghakhanchi, Nepal. Samples were collected in the month of February, 2019 and subjected to direct smear, sedimentation and floatation technique for coprological examination. The study revealed that of the 200 samples examined, 132 samples (66%) were found to be positive for gastrointestinal parasites covering seven genera. The most common parasites were found to be Eimeria sp. (59.5%), Strongyle sp. (33.5%), Trichuris sp. (23%), Haemonchus sp. (14.5%), Strongyloides sp. (13.5%), Trichostrongylus sp. (9%) and Fasciola sp. (4%). Altogether one genera of protozoa and six genera of helminths parasites were found. There was no significance difference between age wise and sex wise prevalence. Single infection was recorded as the highest (54.54%) followed by double (34.09%), triple (7.57%) and multiple (3.78%). From questionnaire survey some common risk factors were recorded during the study period, which were poor farm management system, contaminated food and water, ingestion of contaminated grasses, ingestion of moist aquatic plant near the river and grazing on contaminated field. These factors help to increase the gastrointestinal infections in Goats.